Atenção pré-concepcional de mulheres com diabetes Mellitus pré-gestacional assistidas no Sistema Único de Saúde - Bezerra, Cleide Gomes (2012)
The preconception care for women with Pregestational Diabetes Mellitus (DM) is recognized for its benefits to the woman and the fetus in several countries, and must be guaranteed as a strategy to reduce maternal-fetal morbidity and mortality. We aimed to analyze the preconception care for women with pregestational DM assisted at SUS, aiming to describe the specific route of pregnant women with DM in the SUS health system in Fortaleza, know the clinical and reproductive profile, check the care received in preconception and identify the knowledge regarding maternal and fetal risks. Descriptive and exploratory qualitative study carried out in four reference units for high-risk pregnancies that compose the SUS-Fortaleza, Ceará, Brazil. Data were collected from April to September 2012, involving 41 pregnant women with pregestational DM. We used the triangulation techniques of data collection: interviews, free observation with field notes and revision of the mother’s card and/or of the medical record. The data were organized in tables and received descriptive statistical treatment; the information learned in the field notes complemented the discussion of results. The project was approved by the Ethics Committee of the Universidade Federal do Ceará, according to Protocol number 90/12 and one met the recommendations of Resolution 196/96. The average age of the group corresponded to 30.3 ± 5.3, age of risk for developing DM type 2, the average of education level was 9.4 ± 3.3 years, facilitator aspect for the practice of contraceptive care by women, 76.7% did not plan the current pregnancy, 26.7% were unaware of their type of DM. The prevalent time of diagnosis of DM was up to 10 years, comorbidities were reported by 33.4% of pregnant women; 56.7% of the respondents had between two and four pregnancies, with parity not over four births. The history of miscarriage and stillbirth was expected among women with pre-gestational DM who did not adopt preconceptional care and was present in 40%. About the preconception care needed for this group, the Ministry of Health recommends: glycemic control, replacement of oral hypoglycemic for insulin, control of comorbidities, monitoring of A1C, guidance on hypoglycemia and use of folic acid. Among these, the use of folic acid was being practiced by 10% of pregnant women and glucose monitoring for 6.6% of respondents. Out of these, 10% were receiving the necessary inputs to self-monitoring, when 100% should have it to recognize the best time to gestate. Regarding knowledge about maternal and fetal risks, 60% reported having gotten it in the current pregnancy. We suggest the managers of local public policies to restructure the municipal health system regarding the prenatal care of high-risk and to rescue the preconception attention in primary care.